Is the myonuclear domain ceiling hypothesis dead? - Ferdos Aman; Eman El Khatib; Alanood AlNeaimi; Ahmed Mohamed; Alya Sultan Almulla; Amna Zaidan; Jana Alshafei; Omar Habbal; Salma Eldesouki; Rizwan Qaisar (Singapore Medical Journal)
Muscle fibres are multinuclear cells, and the cytoplasmic territory where a single myonucleus controls transcriptional activity is called the myonuclear domain (MND). MND size shows flexibility during muscle hypertrophy. The MND ceiling hypothesis states that hypertrophy results in the expansion of MND size to an upper limit or MND ceiling, beyond which additional myonuclei via activation of satellite cells are required to support further growth. However, the debate about the MND ceiling hypothesis is far from settled, and various studies show conflicting results about the existence or otherwise of MND ceiling in hypertrophy. The aim of this review is to summarise the literature about the MND ceiling in various settings of hypertrophy and discuss the possible factors contributing to a discrepancy in the literature. We conclude by describing the physiological and clinical significance of the MND ceiling limit in the muscle adaptation process in various physiological and pathological conditions.